c.2 - J. S. Uppal (ed.) (New Delhi, 1984)
On recent visits to India, I had the privilege of exchanging views with my former colleagues about the teaching of economics in the colleges and universities there and abroad. Many of them complained that most of the books on Indian economics now being used are too des criptive-they fail to analyse critically the economic problems facing Indian society. The result is that students, especially at the undergraduate level, do not learn to examine such problems within a theoretical and logical framework. They are unable to grasp as fully as they might the cause-and-effect relationships between different policy variables. Their know ledge of the Indian economy is often restricted to a set of statements, many of which may be based merely on "conventional wisdom".
Keywords: India-Economic conditions